Effects of Xylo-Oligosaccharide on the Gut Microbiota of Patients With Ulcerative Colitis in Clinical Remission - Li, Zongwei; Li, Zhengpeng; Zhu, Liying; Dai, Ning; Sun, Gang; Peng, Lihua; Wang, Xin; Yang, Yunsheng (Frontiers in Nutrition, 2021)
Gut microbiota dysbiosis is closely associated with ulcerative colitis (UC). Prebiotic therapy is a potential approach for UC management especially remission maintaining. Xylo-oligosaccharide (XOS) is an efficient prebiotic with proven health benefits. However, the effects of XOS on the gut microbiota of patients with UC have not been investigated previously. The aim of this study was to evaluate the prebiotic effects of XOS on the fecal microbiota of patients with UC in clinical remission using an in vitro fermentation model. Five patients with UC in clinical remission and 5 healthy volunteers were enrolled in this study. Fresh fecal samples of UC patients were diluted and inoculated in yeast extract, casitone and fatty acid (YCFA) medium alone or with XOS. After fermentation for 48 hours, samples were collected for 16S rDNA sequencing to investigate the gut microbiota composition. Differences in the gut microbiota between healthy volunteers and UC patients in clinical remission were detected using original fecal samples. Subsequently, the differences between the YCFA medium alone or with XOS samples were analyzed to illustrate the effects of XOS on the gut microbiota of UC patients. In both principal coordinate analysis (PCoA)and principal component analysis (PCA), the fecal samples of UC patients differed from those of healthy volunteers. Linear discriminant analysis effect size (LEfSe) analysis revealed that the relative abundances of g_Roseburia and g_Lachnospiraceae_ND3007_group were higher in healthy volunteers than in UC patients, while o_Lactobacillales abundance showed the opposite trend (P<0.05). Wilcoxon rank-sum test bar plot showed that the abundances of g_Eubacterium_halli_group and g_Lachnospiraceae_ND3007_group were higher in the healthy volunteers than in the UC patients (P<0.05). In addition, in UC patients, the Wilcoxon rank-sum test showed that XOS fermentation promoted the growth of bacterial groups including g_Roseburia, g_Bifidobacterium, and g_Lactobacillus, which is beneficial for recovery of intestinal diseases. These results suggest that XOS can relieve dysbiosis in the feces of UC patients in clinical remission and thus represents a potential prebiotic material for maintaining remission.